Factores motivacionales de diseño del trabajo y su relación con desempeño laboral - Raúl Ramírez-Vielma; Gabriela Nazar (Revista Psicologia)
The study addresses the relationship between motivational work design characteristics and different dimensions of individual work performance, adopting an expanded approach to its multidimensionality. Workers from two Chilean organizations (N = 197, 12.7% women, 87.3% men, M = 35.63 years) reported their perceptions of work design and received a performance appraisal by their direct superiors. It was found that the expansion of the meaning and number of performance criteria beyond task performance can play a key role in this relationship. The relationship between the variables of motivational work design and individual performance is modified when considering the emerging dimensions of performance (contextual, adaptive, and proactive). Furthermore, autonomy, as a motivational component of work design, has a greater relationship with adaptive performance and proactive performance than the other motivational work design variables, also demonstrating its predictive potential with respect to performance.